1982
DOI: 10.1111/j.1469-8137.1982.tb03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Aspects of Endomycorrhiza in the Ericaceae

Abstract: SUMMARYThe ultrastructural features of the dissociated mycorrhizal symbionts Pezizella ericae Read and Calluna vulgaris L. Hull, grown in pure culture, and of the modifications occurring in both fungus and root cells during their reassociation in axenic culture have been studied in detail. Growing (apical/subapical and vacuolated zones) and non-growing (ageing zone) regions can be distinguished in colony margins of Pezizella ericae in pure culture. In axenic mycorrhiza cultures the general morphology of the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 25 publications
3
14
1
Order By: Relevance
“…Degeneration of the cortical cell cytoplasm as described in this work has in fact been demonstrated in many ectomycorrhizal associations (Atkinson 1975;Marks and Foster 1973;Harley and Smith 1983) as well as in ericoid (Bonfante Fasolo et al 198 1 ;Bonfante-Fasolo and Gianinazzi-Pearson 1982;Duddridge and Read 1982) and arbutoid mycorrhizae (Fusconi and Bonfante-Fasolo 1984). In these latter two types of mycorrhizae, fungal remnants inside dead root cells were observed as a final developmental stage (Bonfante-Fasolo et al 1981;Bonfante-Fasolo and Gianinazzi-Pearson 1982;Duddridge and Read 1982;Fusconi and Bonfante-Fasolo 1984).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Degeneration of the cortical cell cytoplasm as described in this work has in fact been demonstrated in many ectomycorrhizal associations (Atkinson 1975;Marks and Foster 1973;Harley and Smith 1983) as well as in ericoid (Bonfante Fasolo et al 198 1 ;Bonfante-Fasolo and Gianinazzi-Pearson 1982;Duddridge and Read 1982) and arbutoid mycorrhizae (Fusconi and Bonfante-Fasolo 1984). In these latter two types of mycorrhizae, fungal remnants inside dead root cells were observed as a final developmental stage (Bonfante-Fasolo et al 1981;Bonfante-Fasolo and Gianinazzi-Pearson 1982;Duddridge and Read 1982;Fusconi and Bonfante-Fasolo 1984).…”
supporting
confidence: 70%
“…In these latter two types of mycorrhizae, fungal remnants inside dead root cells were observed as a final developmental stage (Bonfante-Fasolo et al 1981;Bonfante-Fasolo and Gianinazzi-Pearson 1982;Duddridge and Read 1982;Fusconi and Bonfante-Fasolo 1984). This was not observed in ectendomycorrhizae described here.…”
mentioning
confidence: 42%
“…However, it is known that the production of extrahyphal slime can be stimulated by the presence of a potential host (Bonfante-Fasolo & Gianinazzi-Pearson, 1982;Bonfante-Fasolo, Gianinazzi-Pearson & Martinengo, 1984), at least in ericaceous mycorrhizas. The production of this slime is thought to be part of the recognition mechanism between potential mycorrhizal symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…When the fungus is associated with non-host plants, the behaviour of the two organisms contrasts sharply with that observed in mycorrhizal associations. The biotrophic stages of host-fungus interactions in ericoid mycorrhizas, which have now been described in a wide range of naturally and axenically infected host plants (Bonfante-Fasolo & Gianinazzi- Pearson, 1979Pearson, , 1982Peterson, Mueller & Englander, 1980;StruUu & Gourret, 1980;Bonfante-Fasolo et aL, 1981;Duddridge & Read, 1982;Duclos, Pepin & Bruchet, 1983), and which are illustrated in the present work, are characterized at the cellular level by a dramatic increase in the volume of host cytoplasm and proliferation of host organelles. These are both characteristics of metabolically active cells and are normally observed in juvenile plant cells.…”
Section: Non-host Plantsmentioning
confidence: 56%
“…Smith (1979) has suggested that in symbiotic associations the endosymbionts are always enclosed by host membrane if their relation to the host cell has become stabilized and that this sequestration of endosymbionts by host membrane may offer some form of control. If so, the pattern of development of P. ericae in living host cells could be related to the continual presence of the host plasmalemma and coil formation by hyphae of the ericoid endophyte could be interpreted as the result of a direct control by the host plant which limits fungal development so that each cell encloses an individual infection unit (Bonfante-Fasolo & Gianinazzi- Pearson, 1982;Read, 1983). This view is supported by the fact that in the absence of plant plasmalemma around hyphae, as in non-host cells, the fungus grows linearly and unlimited across the root.…”
Section: Non-host Plantsmentioning
confidence: 99%